2021
DOI: 10.1177/15248399211019978
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Systematic Review of Photovoice Projects With Youth in the United States

Abstract: Introduction Photovoice is a method used in community-based participatory research that places cameras in the hands of people and invites them to record their lives, engage in critical dialogue, and advocate for changes needed in their communities. This article presents a review of the literature from 2010 to 2019 on photovoice projects implemented with U.S. youth informed by an emancipatory research conceptual framework. Method Information on 30 project elements was extracted from each of the 47 publications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…This study may be limited by its small sample size, as there were 25 participants. However, many other photovoice studies have less than 20 participants [ 10 , 11 , 13 , 14 , 15 , 22 , 23 , 24 ]. Further, our 25 participants submitted 238 photographs which were analyzed leading to identification of six main themes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study may be limited by its small sample size, as there were 25 participants. However, many other photovoice studies have less than 20 participants [ 10 , 11 , 13 , 14 , 15 , 22 , 23 , 24 ]. Further, our 25 participants submitted 238 photographs which were analyzed leading to identification of six main themes.…”
Section: Discussionmentioning
confidence: 99%
“…The photovoice method provides a means for participants to record and reflect on their situations or surroundings, promote conversation and understanding of personal and/or community issues, and engage community and/or policy stakeholders in dialogue related to situational or community improvements. Photovoice has been applied as a health promotion strategy [ 8 , 9 , 10 ]. Further, Cardarelli et al suggested that photovoice is an especially useful method for researching vulnerable populations which have been either misrepresented or not represented at all by the media [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following the baseline surveys, students in the intervention arm will receive instructions to participate in photovoice 22. This is an established23 24 qualitative participatory method through which adolescents can pictorially take impressions of health facilitators and barriers in their school and community. Pictures will be uploaded onto a secure platform, reviewed and sorted by trained personnel, ensuring that no inappropriate photos are included.…”
Section: Methods and Analysismentioning
confidence: 99%
“…and Making Every School a Health Promoting School emphasise the importance of students’ involvement in health promotion planning, decision-making and implementation in a manner that is empowering. Finally, photovoice facilitates adolescent engagement by allowing them to pictorially take impressions of health facilitators and barriers in their schools and community to inform intervention planning 22–24…”
Section: Introductionmentioning
confidence: 99%
“…However, knowledge about developing critical perspectives on structural systems of oppression is underrepresented in photovoice literature (Liebenberg, 2018;Sanon, Evans-Agnew and Boutain, 2014;Coemans et al, 2019;Derr and Simons, 2020). Multiple (scoping) reviews-in diverse fields-focus on scholars' difficulties to reach policy makers with outcomes of their photovoice project, but they pay little attention to the critical reflection of participants (Dassah et al, 2017;Mysyuk and Huisman, 2020;Han and Oliffe, 2016;Fountain et al, 2021;Suprapto and Sunarti, 2020;Ilagan et al, 2020;Halvorsrud et al, 2021;Lofton and Grant, 2021). Articles that focus on developing critical consciousness with participants remain…”
Section: Introductionmentioning
confidence: 99%